IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM RANAH AFEKTIF BAGI ANAK BEKEBUTUHAN KHUSUS - Hidayati, Eka Wahyu; Ulul Albab, Hayyan Ahmad; Lutfia, Siti (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
Education is needed by all men, including children who are experiencing development. Education must be evenly distributed in all aspects, especially needed by children who have special handling symptoms. Education also does not only include general knowledge, but students also need religious knowledge. This study aims to describe the implementation of PAI learning in the affective realm. This research is included in the type of qualitative research with a descriptive type that describes the data in the field and then analyzes using existing theories. The data collection uses observation, interviews and documentation. The method of analyzing the data uses Miles and Huberman's analysis method with the stages of data collection, data presentation, data condensation and conclusion drawn. How to check the validity of data using data triangulation. The results of this study reveal that the implementation of Islamic religious education in the affective realm for children with special needs at SLB Negeri Gedangan Sidoarjo, by giving more detailed examples and directing more specifically to children with special needs in behaving and socializing well, then teaching habits to children with special needs to carry out religious activities such as reading short letters, congregational prayers in a way that must be accompanied and supervision from teachers.